Family Research and Demographic Analysis (FReDA): Evolution, framework, objectives, and design of "the German Family Demography Panel Study" - Schneider, Norbert F; Bujard, Martin; Wolf, Christof; Gummer, Tobias; Hank, Karsten; Neyer, Franz J (Comparative population studies, 2021)
This article introduces the evolution, framework, objectives, and design of the new data infrastructure "FReDA - The German Family Demography Panel Study", which has been funded by the German Federal Ministry of Education and Research (BMBF) since 2020. FReDA is rooted in the Generation and Gender Survey (GGS) and the German Family Panel (pairfam). FReDA was initiated to facilitate research on family and demography by providing a comprehensive panel study allowing for international comparisons as well as dyadic analyses through a multi-actor design. The survey covers major fields of family research, such as fertility behaviour, reproductive health, work-family conflict, dyadic division of work, gender roles, intimate relations, separation and divorce, parenting and intergenerational relations, social inequalities, family attitudes, and well-being. FReDA interviews are conducted in a self-administered web-based (CAWI) or paper-based (PAPI) manner. The infrastructure consists of two different samples. First, the new FReDA-GGS survey started in early 2021, with a wave 1 study population of individuals aged 18 to 49 years and their partners. Second, the FReDA-pairfam survey will continue the 14-wave pairfam sample from 2022 onwards. The questionnaires of both samples will be harmonised as FReDA evolves. Data accessibility, organisation, and future perspectives of the data infrastructure are described and discussed in the paper's conclusions.